HUBUNGAN KADAR AIR DAN BOBOT ISI TANAH TERHADAP BERAT PANEN TANAMAN PAKCOY PADA KOMBINASI KOMPOS SAMPAH KOTA DAN PUPUK KANDANG SAPI - Henly Yulina dan Wiwik Ambarsari (Program Studi Agroteknologi Faperta UNIBBA, 2021)
The objective of this research was to find out relationship between water content and bulk density to the harvest weight of pakcoy after combined with municipal waste compost and cow manure in Alluvial, Indramayu. This study used a randomized block design factorial with two factors. The first factor is municipal waste compost and the second factor is cow manure. Each of them consisted of 4 levels : 0%, 3.0%, 6.0%, and 9.0% with two replication, followed by regression analysis and linear correlation. The results showed that there was a relationship between water content and bulk density with harvest weight of pakcoy, but the harvest weight of pakcoy was not influenced by water content and bulk density.